Case Report: Midshaft clavicle fracture with concomitant high grade (Type V) acromioclavicular joint dislocation - Cosic, Filip; Ernstbrunner, Lukas; Hoy, Greg A.; Ooi, Keat S.; Ek, Eugene T. (Frontiers in Surgery, 2022)
Introduction Concomitant acromioclavicular joint dislocation and midshaft clavicle fracture are rare injuries, generally resulting from high energy trauma, with limited previous experience in management. Case A 30 year old male presented following a pushbike accident. He had suffered a head on collision with another cyclist. Radiographic examination demonstrated a displaced midshaft clavicle fracture with a Rockwood Type V acromioclavicular joint dislocation. Operative management was undertaken using a dual plating technique. At six month follow up the patient demonstrated full range of motion and had no pain. Conclusion Appropriate radiographic evaluation and careful intraoperative assessment are required using the principles of management for acromioclavicular joint injuries, along with stabilization of the mid-clavicular fracture to reduce the risk of non-union.